Product envelopes: designing positive interplay between brand DNA and customer co-designers. (19th March 2007) - Bardill, Andy; Herd, Kate; Karamanoglu, Mehmet
This paper introduces the product envelope; a new concept which develops the notion and practice of the solution space into a more complete model to support the design of MC product solutions. The product envelope is presented as a model that encompasses the solution space at the core, where the givens and variables of a mass customisable product are described. However, the product envelope also encompasses the less tangible service, interaction and experience touch-points that surround, and provide access to, the tangible MC product that is at the core of the product envelope. A four pleasures analysis is used to reveal the complete model for the product envelope. This product envelope model provides a method whereby designers can take a systematic approach to enabling positive interplay between brand DNA and customer co-designers.